MEK inhibitors cobimetinib and trametinib, regressed a gemcitabine-resistant pancreatic-cancer patient-derived orthotopic xenograft (PDOX) - Kawaguchi, Kei (Oncotarget, 2017)
A pancreatic ductal adenocarcinoma (PDAC), obtained from a patient, was grown orthotopically in the pancreatic tail of nude mice to establish a patient-derived orthotopic (PDOX) model. Seven weeks after implantation, PDOX nude mice were divided into the following groups: untreated control (n = 7); gemcitabine (100 mg/kg, i.p., once a week for 2 weeks, n = 7); cobimetinib (5 mg/kg, p.o., 14 consecutive days, n = 7); trametinib (0.3 mg/kg, p.o., 14 consecutive days, n = 7); trabectedin (0.15 mg/kg, i.v., once a week for 2 weeks, n = 7); temozolomide (25 mg/kg, p.o., 14 consecutive days, n = 7); carfilzomib (2 mg/kg, i.v., twice a week for 2 weeks, n = 7); bortezomib (1 mg/kg, i.v., twice a week for 2 weeks, n = 7); MK-1775 (20 mg/kg, p.o., 14 consecutive days, n = 7); BEZ-235 (45 mg/kg, p.o., 14 consecutive days, n = 7); vorinostat (50 mg/kg, i.p., 14 consecutive days, n = 7). Only the MEK inhibitors, cobimetinib and trametinib, regressed tumor growth, and they were more significantly effective than other therapies (p < 0.0001, respectively), thereby demonstrating the precision of the PDOX models of PDAC and its potential for individualizing pancreatic-cancer therapy.